INHALATION SEDATION IN THOSE WITH SEPSIS-ASSOCIATED DELIRIUM - N. A. Rezepov; O. N. Ulitkina; Yu. V. Skripkin; T. S. Zabelina; V. V. Likhvantsev (Вестник анестезиологии и реаниматологии)
Delirium in the intensive care ward is actively being discussed by anesthesiologists for a long period of time. However at present there are fairly scarce evidences on the efficiency of various techniques of prevention and management of this disorder. Goal of the research: to assess the impact of inhalation sedation on the intensity and duration of sepsis-associated delirium in the intensive care ward of the surgical hospital. Methods. The one-centered, prospective, randomized comparative study was conducted in order to assess the efficiency of inhalation sedation in the patients with sepsis-associated delirium. Propofol was used for the intravenous sedation in the control group. 187 adult patients, admitted to the intensive care ward of Vorokhobov City Clinical Hospital no. 67, were included into the study. Results. Inhalation sedation reduced the delirium duration compared to intravenous use of propofol: delirium was fully managed on the 5th day in the group where sevorane was used [4; 7], while in the group where propofol was used delirium lasted for 7 days [6; 8] (p = 0.03). The study did not detect any effect of inhalation sedation on the intensity of oxidative stress (level of oxidized peptides in the blood plasma of the patients) and degree of neuronal damage (differences between groups are not significant, p = 0.37). No differences were recorded in the value of procalcitonin and SOFA score at any stage of the study. Conclusion. The frequency of delirium in the mixed population of sepsis patients makes 27.9%. Use of inhalation sedation with sevoflurane compared to intravenous administration of propofol reduces the duration of delirium therapy from 7 to 5 days.